2020
DOI: 10.1186/s12985-020-01367-1
|View full text |Cite
|
Sign up to set email alerts
|

Human myoma tissue-based extracellular matrix models for testing the effects of irradiation on the HPV positive cells

Abstract: Background: This study was designed to investigate the invasion of human papillomavirus (HPV) positive human cervical carcinoma cell lines in human leiomyoma-based extracellular matrices in vitro, and to test the suitability of the model for studying the irradiation effects on the cancer cell invasion. Methods: HPV positive cervical carcinoma cell lines SiHa and CaSki, and HPV negative squamous cell carcinoma cell line HSC-3 were used. CaSki cells contain around 600 copies of HPV 16 virus in the genome, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Oral cancer cell lines used in the study, including CAL27 (from tongue), FADU (pharynx), HSC3 (tongue), and TW206 (tongue), were obtained from the Bio-resource Collection and Research Center (BCRC), Taiwan. Those cell lines used in the study are HPV negative [56,57]. FADU cell line carries the R248L hotspot mutation, and no hotspot mutation was found in other cell lines [58].…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…Oral cancer cell lines used in the study, including CAL27 (from tongue), FADU (pharynx), HSC3 (tongue), and TW206 (tongue), were obtained from the Bio-resource Collection and Research Center (BCRC), Taiwan. Those cell lines used in the study are HPV negative [56,57]. FADU cell line carries the R248L hotspot mutation, and no hotspot mutation was found in other cell lines [58].…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…Contamination a b Fig. 7 Levey-Jennings for positive rates of HPV 16 can result in false-positive test findings, which can have serious clinical repercussions. A method indicating the analytical series rejection guidelines, as well as quick tag flagging of a rejection event, should be implemented in each laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Low-risk (LR-HPV) types are linked with benign genital warts [ 5 ]. HPV infection, particularly HR- HPV infection, has been linked to cervical squamous cell carcinoma [ 6 , 7 ]. HPV infections may be temporary [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to growing body of evidence demonstrating the roles of HPV in cancer, each stage of microbe-related cancer diagnosis and treatment was improved remarkably [37,38]. Current therapeutic approaches of HPV associated cancers urgently require the discovery of precise and effective targets underlying HPV invading [39] and DNA viruses transmitting [40]. This study revealed that IGF2BP3, one of the m6A regulators, applied force on the progression and development of HPVrelated CESC.…”
Section: Igf2bp3 Was Related To the Tight Junctions In Hpv-related Cescmentioning
confidence: 97%